Antibacterial activity of cyclo(L-Pro-L-Tyr) and cyclo(D-Pro-L-Tyr) from Streptomyces sp. strain 22-4 against phytopathogenic bacteria. Issue 17 (1st September 2016) - Wattana-Amorn, Pakorn; Charoenwongsa, Waranya; Williams, Christopher; Crump, Matthew P.; Apichaisataienchote, Busaya
Abstract: Two bioactive cyclic dipeptides, cyclo(L -Pro-L -Tyr) and cyclo(D -Pro-L -Tyr), were isolated from the culture broth of Streptomyces sp. strain 22-4 and tested against three economically important plant pathogens, Xanthomonas axonopodis pv. citri, Ralstonia solanacearum and Clavibacter michiganensis . Both cyclic dipeptides were active against X. axonopodis pv. citri and R. Solanacearum with MIC of 31.25  μ g/mL . No activity could be observed against C. michiganensis . Graphical abstract: